The Effect of Spiritual Intelligence and Professional Skepticism of Internal Auditors on Detection of Fraud - Bayuandika, Muhammad; Mappanyukki, Ratna (International Journal of Asian Social Science, 2020)
The research purposes are to prove empirically the effect of spiritual intelligence and professional skepticism on the ability to detect fraud in media companies in DKI Jakarta. The sampling technique used in this study was the saturated sample method with 90 samples. The data collection method used in this study is a questionnaire by distributing questionnaires to internal auditors in private media companies in the DKI Jakarta area. The data analysis technique used to test the hypothesis in this study is Multiple Linear Regression Analysis with the help of the SPSS version 21. The results of this study indicated that the spiritual intelligence variable has no effect on fraud detection whereas professional skepticism has a positive effect on fraud detection. The limitation of this research is that the sample used in this study is limited to only 90 Internal Auditors in the private media companies in DKI Jakarta, which is too few, so the questionnaires obtained are not optimal.